REVIVAL OF THE HOTEL INDUSTRY: THE IMPACT OF FOOD WASTE REDUCTION ON SERBIA’S ECONOMIC PROSPECTS - Gajić, Tamara; Vukolić, Dragan; Penić, Mirjana (Economics of Agriculture, 2024)
Food waste represents a global issue with serious economic, environmental, and social implications. This study investigates the impact of food waste on the economic stability of hotels and restaurants in the Republic of Serbia using a structural modeling approach. The survey included 136 managers across 30 hotels in various cities and mountainous regions of the Republic of Serbia. Results indicate a high awareness of the food waste issue and identify key factors affecting the economic stability of these enterprises. Although no significant link was found between biodiversity, climate, and environment, as well as economy with economic stability, a positive relationship between social environment and economic stability was discovered. This research model provides a deeper understanding of the factors shaping food waste management practices in hotels and restaurants, thereby offering guidelines for enhancing the economic stability of these sectors.